Influence of Material in Circular Splines of Harmonic Reducers on Wear Resistance - Mu Xiaobiao; Ge Yi; Gao Mingyan; Yang Guoqiang; Zhang Chaolei (Jixie chuandong)
Three kinds of circular spline materials are studied for harmonic reducers, stainless steel 2Cr13, medium carbon alloy steel 40Cr, carbon 45 steel. Through the analysis of microstructure, hardness, three-dimensional and two-dimensional morphology in microwear and friction coefficient, the differences in wear resistance of different materials are attained. The results show that the microstructures of 2Cr13 and 40Cr are tempered sorbite, and the microstructure of 45 steel is ferrite and pearlite. The hardness of the 2Cr13 and 40Cr is similar and much larger than that of the 45 steel. The morphology of 2Cr13 is adhesion and spalling, and the wear mechanism is adhesion wear. The morphology of 40Cr and 45 steel is furrow and spalling, furrow and adhesion, and the wear mechanisms are abrasive wear. The friction coefficients' differences of the three materials are negligible, and the area of wear of 2Cr13, 40Cr and 45 steel are 5 008 μm2, 1 645 μm2 and 6 535 μm2. 40Cr exhibits better wear resistance than 2Cr13 with similar hardness. The hardness difference between 45 steel and the friction pair material is the largest, and the wear resistance of the 45 steel is the worst.